Prescribed vs. described: the variability of Spanish mood and tense selection in subordinate clauses of emotive verbs - Welliver, Kelsey (Kansas State University, 2015)
Considerable research exists on subjunctive versus indicative mood patterns of use by both native and L2 speakers of Spanish. Though intermediate level textbooks expose L2 learners to the various tenses of the subjunctive mood, literature has shown that students still struggle with its implementation in their discourse, and various reasons are offered. Little has been done to analyze the prescribed uses that textbooks offer to students regarding mood selection and how these prescribed uses may differ from what Spanish speakers do in real life. The paper first offers a brief explanation of L2 learners’ mood selection in Spanish, followed by a description of Spanish moods and the realis/irrealis dichotomy that is often placed at the center of Spanish mood selection in the literature. Following this, the study offers an analysis of six intermediate level Spanish textbooks’ prescribed uses of two past subjunctive tenses (present perfect and imperfect), as prior research has shown an overlap in the functions of their indicative counterparts. The textbook analysis is then compared to a corpus composed of messages sent on the social media platform Twitter, containing one of six emotive phrases as main clauses, with three in present, three in preterit. The results show that Spanish-speaking users of Twitter employ the prescribed subjunctive mood more often when the verb in the main clause is expressed in the preterit instead of the present, though no such tendency is discussed in the textbooks. The results also reveal an overlap in the functions of the past tense subjunctive moods. The present perfect subjunctive (i.e. haya trabajado ‘has worked’) is used in the subordinate clause nearly 40% of the time with emotive verbal main clauses expressed in the preterit, where the imperfect subjunctive would normally be expected according to prescriptive norms. This pattern of use is not discussed in any of the analyzed textbooks. A discussion of the limitations of the study, implications for textbook writers and further research then follow.
Keywords: Spanish; Linguistics; Subjunctive; Mood selection; Corpus; Prescriptive grammar; Foreign Language Instruction (0444); Language, Linguistics (0290); Language, Modern (0291)